A Study on the Use of ICT Tools in Teaching Geography at the Higher Secondary Level in Madhya Pradesh - Kavita; Tiwari, Neeraj (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
The integration of simple Information and Communication Technology (ICT) tools in classroom teaching has gained importance in improving student engagement and academic performance. Geography, being a subject that requires visual understanding of maps, landforms, climate patterns, and human activities, can benefit greatly from basic ICT tools such as PowerPoint presentations, educational videos, digital maps, and online quizzes. The present study investigates the effectiveness of simple ICT tools in teaching Geography at the higher secondary level in Madhya Pradesh. A sample of 50 Class XI students from two government schools in Bhopal was selected. A single-group pre-test and post-test experimental design was used. After traditional teaching, students were exposed to four weeks of ICT-supported instruction using PowerPoint slides, YouTube educational videos, digital maps, and projector-based lessons. The findings revealed significant improvement in academic achievement. The mean score increased from 28.4 (pre-test) to 40.6 (post-test). A paired sample t-test showed a statistically significant difference (t = 7.92, p < 0.001). The study concludes that even simple and low-cost ICT tools can significantly improve Geography learning outcomes at the higher secondary level.